2017
DOI: 10.14198/ingeo2017.68.01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the North Atlantic Subtropical High on wet and dry sea-breeze events in North Carolina, United States

Abstract: The sea-breeze (SB) is an important source of summertime precipitation in North Carolina (NC, southeast United States). However, not all SB events produce precipitation. A climatology of wet and dry SB events in NC is used to investigate the conditions that are conducive to precipitation associated with the sea breeze.Radar imagery was used to detect 88 SB events that occurred along the NC coast between MaySeptember of 2009-2012. The majority (85%) of SB events occurred during offshore flow (53%) or during flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…On daily timescales, Luchetti et al . (2017) found that the NASH western ridge helps control moisture availability and winds along the North Carolina coast, thus providing a synoptic‐scale control mechanism for sea breeze precipitation. In particular, they showed that when the NASH western ridge is located along the southeast coast of the United States, its associated moist southwesterly flow along the North Carolina coast favours the occurrence of precipitation along the sea breeze front.…”
Section: Introductionmentioning
confidence: 99%
“…On daily timescales, Luchetti et al . (2017) found that the NASH western ridge helps control moisture availability and winds along the North Carolina coast, thus providing a synoptic‐scale control mechanism for sea breeze precipitation. In particular, they showed that when the NASH western ridge is located along the southeast coast of the United States, its associated moist southwesterly flow along the North Carolina coast favours the occurrence of precipitation along the sea breeze front.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this, studies suggest that the highs in the Northern Hemisphere 29 and Southern Hemisphere 30 subtropical oceans are becoming more intense and expanding landward, leading to a greater moisture flux into the CZ. Sea-breeze circulations (SBC) are also dependent on the land-ocean thermal contrast, and the added moisture and energy would be conducive to the generation of mesoscale precipitation fronts that can penetrate further into the interior 31 . Furthermore, if the interior has higher elevations oriented along the coastline, this would result in a greater frequency of orographically enhanced rainfall, boosting the upward trend 11,13 .…”
Section: Discussion Of Potential Mechanismsmentioning
confidence: 99%